(untitled) (Research, Society and Development, 2022)
The vast majority of studies on deferring blood donors target large blood banks that supply most of the blood supply for medical purposes. However, smaller blood collection services are still important at the local level and their donors may have different demographic and epidemiological characteristics. To highlight the epidemiological profile of blood donors and the probabilities of inability to donate blood in Brazil. A systematic review of the literature was carried out, where the results of the main studies contained in the scientific databases SciELO, LILACS and PubMed in Portuguese and English, and data from ANVISA were collected. 17 articles were selected that fit the objectives and inclusion criteria. A table and three graphs were prepared with the purpose of presenting the main information collected in an objective way. The permanent analysis of the epidemiological profile and probabilities of inability to donate blood in Brazil serves as a subsidy for public policies, to promote actions to attract donors, stimulating future actions of blood donations.